Does gratitude correlate with positive thinking? - Wustari L Mangundjaya; Nurul Syamsiyah (Jurnal Scientia, 2024)
Indonesia experienced the COVID-19 pandemic in 2020, causing many impacts, such as economic downturn, resulting in the huge of employment termination.. This has an impact on employees who experience layoffs during the COVID-19 Pandemic. During this condition, individuals to always be grateful and think positively in facing these conditions. The aim is to express the relationship between gratitude and positive thinking in employees who have been laid off, namely men who are employees who have been laid off and can provide solutions. This method uses quantitative with a correlational approach. Data was collected using 2 types of questionnaires, namely gratitude and positive thinking. There were 99 male respondents from the Tambun area who were laid off from the company due to the economic downturn in the company. The research results show that there is a significant positive relationship between feeling grateful and positive thinking. The greater the feeling of gratitude, the greater the sense of positive thinking that layoff victims have. The research results can be used to minimize the negative feelings of layoff victims so that layoff victims can again accept everything that happens with gratitude and enthusiasm to live their daily lives, namely with positive thoughts.